The Oxford handbook of organizational decision making - Hodgkinson, Gerard P., 1961-; Starbuck, William H., 1934- (Oxford : Oxford University Press, 2008)
This handbook comprehensively surveys research on organizational decision-making. It looks at decision-making at the level of individuals, groups, organizations, and inter-organizations emphasizing psychological perspectives while encompassing insights from economics, political science, and sociology.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Decision making; Organizational behavior